Sleep Apnea Is Associated with Cardiovascular Risk Factors among Kidney Transplant Patients - Molnar, Miklos Zsolt (American Society of Nephrology, 2010)
Background and objectives: We assessed the prevalence of obstructive sleep apnea (OSA) and its clinical correlates in a large sample of patients who received a kidney transplant (Tx). We also compared the prevalence of the disorder between dialysis patients who were on the waiting list for a Tx (WL) and Tx patients. Design, setting, participants, & measurements: This was a cross-sectional study of 100 Tx and 50 WL patients who underwent one-night polysomnography (SLeep disorders Evaluation in Patients after kidney Transplantation [SLEPT] Study). Sociodemographic information and data about medication, comorbidity, and laboratory parameters were collected. Results: The prevalence of mild (apnea-hypopnea index [AHI] ≥5/h and <15/h), moderate (AHI ≥15/h and <30/h), and severe OSA (AHI ≥30/h) was 18, 11, and 14% in the Tx group and 28, 16, and 10% in the WL group, respectively. The AHI was significantly correlated with age (ρ = 0.34), body mass index (ρ = 0.45), neck circumference (ρ = 0.4), abdominal circumference (ρ = 0.51), and hemoglobin (ρ = 0.24) in the Tx group. The proportion of Tx patients who were treated with three or more antihypertensive drugs was significantly higher in the OSA group (56 versus 31%; P = 0.022). Despite taking significantly more antihypertensive drugs, the average systolic BP was still higher in patients with versus without OSA (147 ± 21 versus 139 ± 18 mmHg; P = 0.059). Conclusions: The prevalence of OSA is similar in Tx and WL patients and it may contribute to presence of hypertension in patients who receive a Tx.